Analysis of Factors Affecting Broad Money of Five ASEAN Countries - Bara' Tiku, Intan; Abd. Rahim; Sri Astuty; Diah Retno Dwi Hastuti; Muhammad Syafri (PT Inovasi Pratama Internasional, 2025)
This study evaluates the factors that influence the broad money of five ASEAN countries. Global economic uncertainty due to financial crises, geopolitical conflicts and pandemics has affected the region's economic stability. Central banks have a role in controlling broad money through monetary policy, but its effectiveness is affected by other factors such as GDP, interest rates and inflation. Moreover, the relationship between GDP growth, inflation, and interest rates with broad money is a major concern, as the trend of broad money growth in the 5 ASEAN countries continues to increase every year. The balance between broad money and price stability is crucial to prevent economic stress that could lead to a recession. Therefore, this study focuses on an in-depth analysis of the factors that influence money supply to help the government make decisions. The research sample consists of 100 data with five ASEAN countries, namely Vietnam, Indonesia, Thailand, Philippines and Malaysia with a time series of 2004-2023. This methodology uses a mixed approach, namely quantitative with secondary data from the World Bank & IMF with LSDV analysis. It was found that the adjusted r square value was 97%, which means that GDP, interest rates, and inflation used were able to explain the money supply of 5 ASEAN countries by 97% and 3% was influenced by other factors outside this study. GDP was found to have no significant effect while interest rates have a significant negative effect and inflation has a significant positive effect on the broad money of 5 ASEAN countries. The government is expected to better analyze the policies and actions taken, such as managing monetary policy wisely, especially in maintaining the stability of inflation and interest rates so that the money supply can be well controlled.